The National Question in the Kingdom of Serbs, Croats and Slovenes. The Croatian Case - Becherelli, Alberto (Richtmann Publishing, 2011)
The dissolution of the multinational State of Yugoslavia after a half century of Socialistic regime and its violenttransformation into several independent States during the 90â€™s renewed the debate about the origins and the development of the â€œYugoslavnational questionâ€. The paper describes how the foundation of the Kingdom of Serbs, Croats and Slovenes after the WWI was anunsuccessful attempt to create a modern and unitary Nation-State for the Croats and the other Yugoslav nationalities.